Tacit coordination in games with third-party externalities - James Bland; Nikos Nikiforakis (Max Planck Institute for Research on Collective Goods, 2013)
When agents face coordination problems their choices often impose externalities on third parties. We investigate whether such externalities can affect equilibrium selection in a series of one-shot coordination games varying the size and the sign of the externality. We find that third-party externalities have a limited effect on decisions. A large majority of participants in the experiment are willing to take an action that increases their income slightly, even if doing so causes substantial inequalities and reductions in overall efficiency. Individuals revealed to be other-regarding in a non-strategic allocation task often behave as-if selfish when trying to coordinate.
Keywords: D63; D01; D62; C90; D03; 330; social preferences; efficiency; externalities; tacit coordination; equilibrium selection